Differential contribution of CBP:CREB binding to corticotropin-releasing hormone expression in the infant and adult hypothalamus - Cope, Jessica L. (2013)
Corticotropin-releasing hormone (CRH) contributes crucially to the regulation of central and peripheral responses to stress. Because of the importance of a finely tuned stress system, CRH expression is tightly regulated in an organ- and brain region-specific manner. Thus, in the hypothalamus, CRH is constitutively expressed and this expression is further enhanced by stress; however, the underlying regulatory mechanisms are not fully understood. The regulatory region of the crh gene contains several elements, including the cyclic-AMP response element (CRE), and the role of the CRE interaction with the cyclic-AMP response element binding protein (CREB) in CRH expression has been a focus of intensive research. Notably, whereas thousands of genes contain a CRE, the functional regulation of gene expression by the CRE:CREB system is limited to ~100 genes, and likely requires additional proteins. Here, we investigated the role of a member of the CREB complex, CREB binding protein (CBP), in basal and stress-induced CRH expression during development and in the adult. Using mice with a deficient CREB-binding site on CBP, we found that CBP:CREB interaction is necessary for normal basal CRH expression at the mRNA and protein level in the nine-day-old mouse, prior to onset of functional regulation of hypothalamic CRH expression by glucocorticoids. This interaction, which functions directly on crh or indirectly via regulation of other genes, was no longer required for maintenance of basal CRH expression levels in the adult. However, CBP:CREB binding contributed to stress-induced CRH expression in the adult, enabling rapid CRH synthesis in hypothalamus. CBP:CREB binding deficiency did not disrupt basal corticosterone plasma levels or acute stress-evoked corticosterone release. Because dysregulation of CRH expression occurs in stress-related disorders including depression, a full understanding of the complex regulation of this gene is important in both health and disease.